Karakterisasi Edible Film Pati Sagu Alami dan Termodifikasi - Febby J. Polnaya; Haryadi Haryadi; D.W. Marseno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
This research was conducted to use native sago starch (PSA), hydroxypropyl sago starch (PSHP, molar substitutions (MS) 0.058) and hydroxypropyl-acetyl sago starch (PSHP-AS MS 0.058; degree of substitutions (DS) 0.061) as basic materials for edible film, prepared with 3, 4 and 5% w/v. Edible film solution was prepared at 70oC for 30 min with glycerol (0.5% w/v) addition as plasticizer, and then dried-up using oven at 40oC. Analysis was conducted for physical characteristics of edible films including film thickness, elongation, tensile strength, water vapor transmission rate (WVTR), and solubility. Sago starch film produced by PSA, PSHP (MS 0.058) and PSHP-AS (MS 0.058-DS 0.061) showed different characteristics compared to PSA, including thickness, tensile strength, elongation, and WVTR of the films. The best edible film produced by PSHP‑AS (5%, w/v) with lowered WVTR was 11.27 g H2O/m2 h, its thickness was about 0.085 mm, tensile strength was 13.91 MPa, elongation was 0.32% and solubility was 90,595%.